Pelaksanaan Reklamasi Lahan Bekas Tambang di Wilayah Izin Usaha Pertambangan Tanah Urug Tjong Lie Ko, Kabupaten Sambas, Provinsi Kalimantan Barat - Muhammad Hery Setiyawan; R. Andy Erwin Wijaya (Retii, 2022)
In order to implement the commitment to environmental impact management responsibility for landfill mining activities from 2018 to 2022, the owner of the mining license Tjong Lie Ko has currently carried out his obligations in reclamation activities of ex mining area. The total realized area of ​​land clearing that has been cleared from 2018 to 2022 is 4.75 hectares. The total land clearing consists of a mining area of ​​3.70 hectares and an area of ​​mining infrastructure of about 1.05 hectares. Mining facilities and infrastructure that have been built include mine roads, root zones, sediment ponds, employee housing, offices, and mechanical utilities. The planned reclamation program on ex-mining area that is regrading on ex-mining area, revegetation, regrading on sediment ponds and handling acid mine drainage. Land use of ex-mining area at the location of Tjong Lie Ko's mining license is carried out of converting ex-mining land into plantations and converting settling ponds into plantation ponds and reservoir. The realization of reclamation costs consisted of direct costs of Rp. 59,633,345,- and indirect costs of Rp. 16,399,170,-, so the total cost incurred by Tjong Lie Ko to carry out reclamation in 2018-2022 was Rp. 76,032,515,- .